The 20th century zeitgeist in Doris Lessing's fiction: a reading of the children of violence series - Bhuiyan, Robina Rashid (BRAC University, 2011)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2011.